Theoretical aspects of high-spin states - Leander, G. A.; Arve, P.; Bengtsson, T.; Ragnarsson, I.; Zhang, J. Y. (Nuclear Physics, Section A, 1983)
First, nuclear shapes are considered with focus on the γ degree of freedom and the unexplored high-spin regions of negative γ. Next, the role of approximate quantum numbers for very high-spin spectroscopy is examined, using as an example a calculation for 160Er which is related to available quasicontinuum data. The trend from regular to chaotic behavior is discussed in the broader context of theoretical mechanics.